ANALISIS STATISTIK MULTIVARIATE UNTUK MENDAPATKAN WAKTU LOSSETIME OPTIMAL ALAT GALI MUAT DAN ALAT ANGKUT DALAM MENCAPAI TARGET PRODUKSI PENGUPASAN OVERBURDEN DI PIT TIMUR PT. ALLIED INDO COAL JAYA, PARAMBAHAN, SAWAHLUNTO - M. Ilham Khalid; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2021)
Based on the overburden stripping production data in the East Pit, Mining Work Unit PT. Allied Indo Coal Jaya. October 2020 for 2 mining fleets, are around 77.963,41 Bcm. From the actual production above, it is known that the overburden production target for 2 mining fleets is 110.000 Bcm, so it can be concluded that the stripping production target in October 2020 was not achieved. Based on data on working hours of mining equipment, the percentage of utilization of the available working time of the EU (Effective Utilization) for 2 mining fleets is 72% and 75%, respectively. From these problems, the percentage of utilization of the EU's available working time (Effective Utilization) has not been used optimally. From the problems above, it is necessary to do an optimal losstime analysis to meet the production target of overburden stripping. The analysis that will be used in this study is multiple linear regression analysis using the least squares method in estimating multiple linear regression coefficients. The purpose of this analysis is to obtain an optimal mathematical model of losstime in meeting the production target of overburden stripping in October 2020.Keywords: Production, lossetime, optimal time, linear regression analysis double, least squared